Normalization of working conditions in premises of special purpose methods of artificial airionization - Толкунов, Ігор Олександрович (Eastern-European Journal of Enterprise Technologies, 2014)
The paper deals with solving important scientific and technical problem of ensuring safe working conditions for the personnel of departments of the State Emergency Service of Ukraine, which is to normalize working conditions in special-purpose premises using artificial bipolar air ionization of working environment. It is shown that using modern ventilation and conditioning systems deionize air in the working areas of premises, depriving it of natural ionic composition. This negatively affects the general personnel condition of departments and their efficiency as a whole. Herewith, normative concentration level of light air ions in specialpurpose premises can be achieved using artificial air ionization methods, the implementation of which requires specific data on the air ion concentration field formation mechanism in the air of working areas. The design of adjustable bipolar corona air ionizer was developed, and relations, allowing to determine its design and operating parameters were defined. The analytical relations, the adequacy of which was confirmed experimentally, reveal the air ion concentration field formation mechanism in supply jets of ionized air that allows to estimate the working area air ion mode parameters under their direct influence. Using the developed device in special-purpose premises will ensure the implementation of occupational safety air ionization requirements and guaranteed safety of their operation, as well as high efficiency of artificial air ionization measures with their implementation cost reduction that is caused by the possibility of using engineering calculation methods in the design and manufacture of devices, based on the corona discharge effect.